1995
DOI: 10.1038/sc.1995.144
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sexual functioning in women following spinal cord injury

Abstract: Research into sexuality following spinal cord injury (SCI) has tended to concentrate on male experiences and the physical capabilities for sexual intercourse. The sexuality of women following SCI has only recently been addressed and studies are limited to small numbers and the use of non-standardised measures. The present investigation utilised standard measures of affective state and body satisfaction together with pre and post-injury questionnaire information of sexual dysfunction, feelings about sex and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 8 publications
3
30
0
5
Order By: Relevance
“…1 There are few studies which assess the impact that SCIs have on the sexuality of women, and the majority which do so are focused primarily on reproductive aspects. [2][3][4][5] The reasons behind this fact may probably be explained by the much higher incidence of SCI in men than in women, [5][6][7] by the belief that female sexual dysfunction is less problematic given their supposed passive role during sexual intercourse, 5,8 and by the greater objectivity of loss of erection, ejaculation, and male fertility. 6,7 Sexuality constitutes a fundamental part of people's lives, integrating physical, emotional, intellectual, and social aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 There are few studies which assess the impact that SCIs have on the sexuality of women, and the majority which do so are focused primarily on reproductive aspects. [2][3][4][5] The reasons behind this fact may probably be explained by the much higher incidence of SCI in men than in women, [5][6][7] by the belief that female sexual dysfunction is less problematic given their supposed passive role during sexual intercourse, 5,8 and by the greater objectivity of loss of erection, ejaculation, and male fertility. 6,7 Sexuality constitutes a fundamental part of people's lives, integrating physical, emotional, intellectual, and social aspects.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Sexuality constitutes a fundamental part of people's lives, integrating physical, emotional, intellectual, and social aspects. 5 A spinal injury may affect the patient's sex life not only due to the physical impairments, but also owing to a lower self-esteem and self-image, as well as the attitude that both society and their partners show towards disability. 9 There is still a tendency in society to regard the disabled as asexual, always dependent on others and unable to have physical relationships on equal terms.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,8,9 Women have also indicated that their emotional needs were inadequately supported during rehabilitation. 1,6,10 Pentland et al 9 (p 19) for example, noted how women interviewed for a study on ageing and SCI, 'spoke with much bitterness about the neglect of their y emotional adjustment needs during rehabilitation'. Moreover, women have described a frustration with an overemphasis on sport, competition and physical outcomes during rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is not clear whether the item titled 'sexual dysfunction' is referring to sexual dysfunction or sexual dissatisfaction. 19 Similarly, for the item titled 'bladder dysfunction'. Again, it is not clear whether this refers to the bladder dysfunction, which the majority of people with SCI would experience, or whether it is referring to secondary problems related to bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%